2017
DOI: 10.5812/iji.15591
|View full text |Cite
|
Sign up to set email alerts
|

Cholera in Niger Republic: An Analysis of National Surveillance Data, 1991 - 2015

Abstract: Background: Cholera is an infectious disease caused by a gram negative bacteria, Vibrio cholerae. It was found for the first time in Niger during year 1970 and continues to occur as an issue of major public health importance. Objectives:This study aimed at more accurately defining the burden of cholera in Niger. Methods: Cholera surveillance data from the direction of epidemy surveillance and response reported to the Niger ministry of public health and the world health organization were reviewed and analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…If most patients have signs and symptoms compatible with the working diagnosis, and, perhaps, 15% to 20% are laboratory-confirmed, countries do not need more confirmation (32). The finding was similar to the studies conducted in Niger (33) and Kenya (34) where very low proportion of bacteriologically confirmed cases were observed which limits the reliability of information available to guide prevention and control strategies. Although laboratory capacity to support routine surveillance has been weak, improvements were observed in microbiological testing capacity and laboratory data management overtime on using both rapid diagnostics tests and culture.…”
Section: Discussionsupporting
confidence: 70%
“…If most patients have signs and symptoms compatible with the working diagnosis, and, perhaps, 15% to 20% are laboratory-confirmed, countries do not need more confirmation (32). The finding was similar to the studies conducted in Niger (33) and Kenya (34) where very low proportion of bacteriologically confirmed cases were observed which limits the reliability of information available to guide prevention and control strategies. Although laboratory capacity to support routine surveillance has been weak, improvements were observed in microbiological testing capacity and laboratory data management overtime on using both rapid diagnostics tests and culture.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, the finding by Alkassoum et al (2019) revealed that the trend of cholera incidence was peaked during the rainy season. According to research by Manzo et al (2017), the Niger Republic's case fertility rate increased from 2.0 to 7.8% between 2012 and 2015 as a result of fewer people having access to clean water and adequate sanitation. The majority of assessments also stated that lowor middle-income nations were where the cholera epidemic first emerged.…”
Section: Discussionmentioning
confidence: 99%